The Environmental assessment of drilling system groundwater in Merced community, canton Colta, Chimborazo (Revista Científica Ciencias Naturales y Ambientales, 2015)
This study evaluated the generation of environmental impacts in the groundwater drilling project and designed a possible plan of environmental management according to social, economic and environmental characteristics of the study area. The result of the environmental impact assessment identified that the main problems are: the generation of solid waste and hazardous and non-hazardous liquid, gaseous emissions, noise and vibration produced by mechanical equipment, as well as risk of accidents and occupational diseases caused by work at height and mechanical work. The socioeconomic analysis by field surveys showed as a result, La Merced community is represented mainly by people from the indigenous ethnic group, whose main source of income is agriculture and livestock; access to health and the provision of basic services is inadequate. Currently, the population has serious problems by shortage of drinking water, which is a trigger for disease and death of the most vulnerable sectors of the study area. The drilling project for exploitation of groundwater has a high percentage of acceptances as it will improve the poverty by unsatisfied basic needs.
Keywords: Baseline; Chimborazo; Colta; drilling; environmental impacts; environmental management plan